The effect of a Lactobacillus-based probiotic for the control of necrotic enteritis in broilers - Layton, Sherryll Lynn; Hernandez-Velasco, Xochit; Chaitanya, Shivaramaiah; Xavier, Jorge; Menconi, Anita; Latorre, Juan David; Kallapura, Gopala; Kuttappan, Vivek Ayamchirakkunnel; Wolfenden, Ross Elderon; Andreatti Filho, Raphael Lucio [UNESP]; Hargis, Billy Marshal; Tellez, Guillermo (My University, 2013)
Necrotic Enteritis (NE) caused by Clostridium perfringens (CP) in poultry is probably the most important bacterial disease in terms of economic implications. The disease is multi-factorial and is invariably associated with predisposing factors. The present study investigated the effect of a commercially available Lactobacillus-based probiotic (FM-B11) for the control of necrotic enteritis in broiler chickens. In experiment 1, one-day-of-hatch broiler chicks were randomly allocated to the following treatment groups: 1) Non-challenged (NC); 2) Challenged (C); 3) Challenged + probiotic (C+ FM-B11). Prior to placement, chicks in groups 2 and 3 received 0.25 mL of Salmonella typhimurium (ST) containing 105 cfu of viable cells by oral gavage. At 14, 15 and 16 days of age, all chicks in group 3 were treated with FM-B11 in the drinking water at a concentration of 106 cfu/ml. At 21d of age, all chicks in groups 2 and 3, were individually challenged with 5 × 104 sporulated oocysts of E. maxima by oral gavage. At 26d of age, all chicks in groups 2 and 3, were individually challenged with 108 cfu CP; body weight (BW) was recorded prior to challenge. The experiment was terminated at 29 days of age and the following parameters were evaluated: NE-associated mortality, CP lesion scores, CP concentrations in ileum, BW, and body weight gain (BWG). Chicks treated with FM-B11 had significantly (P < 0.05) higher body weight gain after challenge when compared to control challenge chickens. Total mortality was higher in the C group (48.8%) when compared to the C + FM-B11 (12.7%). Even though there was no significant (P > 0.05) difference in lesion score between C and C + FM-B11, group C + FM-B11 had significantly (P < 0.05) lower total number of cfu of CP recovered from the ileal mucosa and content samples when compared to group C. Experiment 2 was a unique and remarkable case report of a field outbreak of NE in a commercial broiler farm in Argentina. A reduction and control of the mortality associated with NE following 3 days of administration of FM-B11 was observed as compared with the control non treated house. These results imply that the commercially available Lactobacillus-based probiotic FM-B11 was able to reduce the severities of NE, as a secondary bacterial infection, in an experimental NE challenge model; as well as, in a commercial field outbreak of NE.
Keywords: Lactobacillus; Necrotic enteritis; Salmonella; Coccidiosis; Probiotic